Increasing Moral Emotions Through Traditional Games of Gobak sodor and Bentengan Using the Experiential Learning Method - Iswinarti Iswinarti; Wahyu Nur Laily (Universitas Muhammadiyah Surakarta, 2024)
The decline in morality has been of interest in the education world, especially among junior high school students. They tend to justify their mindset and actions when making decisions about problem-solving. Moral emotion is an essential aspect to have before any decision-making. Students must have moral emotions to avoid repeating mistakes and bad behavior. Efforts to increase moral emotions through the traditional game